ELECTRONIC VOTING AND THE ELECTORAL PROCESS: NOTES ON THE SECURITY OF ELECTRONIC BALLOT BOXES (CIPEEX, 2025)
Electronic voting represents a technological advance in the Brazilian electoral system, replacing paper ballots with electronic ballot boxes since 1996. This model aims at greater agility, reliability, security, and transparency in elections, ensuring the legitimacy of the electoral process. This work aims to investigate, based on academic, normative and institutional studies, the security mechanisms of the electronic voting system in Brazil, evaluating its effectiveness in preventing fraud and its contribution to the legitimacy of the electoral process. A bibliographic and documentary research was carried out, based on technical studies of the Superior Electoral Court (TSE), Electoral Justice and independent audit reports, the interpretative method is presented by the compilation of the study of the direct documentation addressed, on a qualitative approach. In view of this, the data indicate that the Brazilian electronic voting system adopts the Linux system (Uenux), multiple layers of security, such as encryption, physical seals, public security tests and internal and external audits. However, criticism persists, especially regarding the absence of a printed proof of vote, as it makes some people defend this idea in order to increase transparency and reinforce confidence in the system. We conclude, therefore, that electronic voting is currently a safe and efficient system, as demonstrated by the technical evidence and the absence of fraud proven in previous elections, according to the Electoral Court. However, transparency and public trust can be increased with the adoption of additional measures, such as the auditable printed vote, as long as the secrecy and integrity of the vote are not compromised.
Keywords: Electronic voting; Electoral security; Electronic ballot box; Democratic process